Antioxidant activity of rooibos tea (Aspalathus linearis) in model lipid and radical generating systems - Winterton, Paula (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc. in Food Science) -- University of Stellenbosch, 1999.